Hyperinflation and the Dynamics of the Demand for Money in China, 1945-1949 - Hu, Teh-wei (Journal of Political Economy, 1971)
This paper is to study the demand for money during the Chinese inflation of 1945-49. Based on the Chinese experience, the results confirm the hypothesis that during hyperinflation the expected rate of change in prices is the most important variable in the demand function for money. The estimated value of the coefficient of cash balances adjustment is close to one. Thus, the assumption that the desired level of real cash balances tends to equal the actual level during hyperinflation is supported.